Task orientation, knowledge sharing, organizational justice, and organizational commitment among bank employees: Evidence from Nigeria - Akeem Adekunle Kenku; Benjamin Adegboyega Olabimitan; Ajibola Abdulrahamon Ishola (Department of Management | Faculty of Economics and Business | Universitas Diponegoro, 2022)
The challenges facing banking organizations have manifested in low job commitment among employees. This was attributed to poor task orientation, low knowledge sharing, and a lack of organizational justice in these organizations. However, to the researchers' knowledge, only a few studies outside the Ibadan metropolis have investigated the contribution of the identified variables to the current level of organizational commitment among bank employees in Nigeria. The cross-sectional survey polled responses from 406 employees conveniently sampled from selected bank branches in Ibadan using a standardized questionnaire. The results revealed significant positive associations among task orientation, knowledge sharing, organizational justice, and dimensions of organizational commitment. Task orientation, knowledge sharing, and organizational justice significantly influenced organizational commitment. The study recommends more studies be conducted on investing in employees' knowledge capital, training, and promoting justice as these foster high organizational commitments and spur optimum job performance.